(untitled) (Polish Yearbook of International Law, 2022)
In the summer of 2021 deliberate actions by the Belarusian state authorities led to a huge increase of people irregularly crossing the border from Belarus to Poland. Instead of addressing this humanitarian crisis, the Polish government responded with actions that were in violation of its international obligations and domestic law. Among these measures was carrying out “pushbacks” and grounding them in Polish domestic law. “Pushbacks” are the practice of returning people to the border without assessing their individual situation. The formalization of those practices in 2021 was done within two legal frameworks; one interim and one permanent. They continue to function in parallel while containing diﬀerent provisions. This article assesses the two frameworks’ compatibility with domestic and international law and concludes that they both violate domestic and international rules. In the context of EU law, the article demonstrates the incompatibility of the two frameworks with the so-called Asylum Procedures Directive and Return Directive. The article urther argues that the pushbacks violate the European Convention of Human Rights and would not fall within the exceptions to the prohibition of collective expulsions.